Structure and ultrastructure study on photophores of the Madeira lanternfish, Ceratoscopelus maderensis (Lowe, 1839), Pisces: Myctophidae. (16th December 2017) - Cavallaro, Mauro; Battaglia, Pietro; Guerrera, Maria Cristina; Abbate, Francesco; Levanti, Maria Beatrice; Ammendolia, Giovanni; Andaloro, Franco; Germanà, Antonino; Laurà, Rosaria
Abstract: The structure and ultrastructure of photophores in the Madeira lanternfish, Ceratoscopelus maderensis, from the Strait of Messina (Mediterranean Sea) was investigated. The structure of C. maderensis photophore observed by light microscope consists of different functional parts: the photogenic cells, involved in the light production process, and a set of dioptric annexes, such as the accessory scales, lens‐scale, reflector and pigmented layer. The photocytes have an elongated, thin and flattened shape and are located inside a cup‐shaped structure, made up of the reflector and the pigmented layer. The lens‐scale has a protection function as well as a dioptric role and is covered by accessory scales. The innervation of the lens‐scale of C. maderensis and the other structures having a neurotransmitter function are probably implicated in the regulation of intensity and direction of light emission as well in playing a role in the counterillumination camouflage in the mesopelagic environment. The anatomical description of the photophores of C. maderensis provides a scientific basis for future investigations on the functioning of photogenic systems in relation to the ecology of this mesopelagic fish.